Ամլության խնդրի ժամանակակից լուծումները - Խմբ.՝ Առաքել Առաքելյան (1944-1948); Լևոն Կիսիբեկյան (1948-1950); Աշոտ Աբրահամյան (1950-1955); Առաքել Առաքելյան (1955-1956); Արթուն Հատիտյան (1956-1982); Պարգեւ Շահբազյան (1983-1984); Երվանդ Մելքոնյան (1985-1993); Տ. Ասողիկ եպս. Արիստակեսյան (1994-1996); Տ. Բագրատ աբղ. Գալստյան (1996-1998); Մարիամ Վարդանյան (պաշտոնակատար) (1998-1999); Տ. Արշակ աբղ. Խաչատրյան (պաշտոնակատար) (1999); Անդրանիկ Զեյթունյան (2000-2001); et al. (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Сегодня как никогда технологии занимают важное место в гармоничных отношениях человека и природы, оказывая на них заметное влияние и одновременно бросая новые вызовы. Имея в виду актуальность темы, статья рассматривает вопросы касающиеся проблеме бесплодия с применением “достижений” современных медицинских технологий. Вопрос дискутируется с точек зрения практики и морали, подчеркивается необходимость осторожного обращения со “всемогуществом” медицины при рассмотрении проблем происхождения человека и его дальнейшего развития. Today, more than ever, technology has an important place in the harmonious relations of human beings and nature, at the same time leaving its notable influence and creating new challenges. Taking into consideration the actuality of the issue, the article reflects on the resolution of the problem of infertility through the help of technology which is accepted as “achievement” for the medical sphere. The problem is considered from practical and moral viewpoints and highlights the necessity to be careful towards the “supremacy” of the medicine in analyzing issues of the origin and further development of human beings.
Keywords: Medicine; Christianity